Effects of Mediterranean dehesa management on epiphytic lichens. - Aragón, Gregorio; López, Rubén; Martínez, Isabel (The Science of the total environment, 2010)
Spanish holm oak (Quercus ilex subsp. ballota) open woodlands (dehesas) maintain a high diversity of plants and animals compared to other forested Mediterranean habits, but little is known about the responses of epiphytic lichens to different management regimes that are applied to this woodland type. The present study was carried out in central-southern Spain and included four management regimes: agriculture, grazing of sheep, grassland grazed by wild ungulates (deer), and abandoned dehesas covered by shrubs. Total species richness and cover exhibited considerable variation among management regimes. Both parameters tended to decrease with the intensity of management, abandoned dehesas maintaining a higher number of species than more intensively managed habitats. Lichen composition also significantly differed among the four regimes. Nitrophytic species were clearly associated with more intensive management regimes (farming or livestock management), whereas non-nitrophytic species favored abandoned dehesas.
The following values have no corresponding Zotero field: publisher: Elsevier B.V. accession-num: 20937519
Keywords: Lichen composition; Mediterranean Spain; Nitrophytic specie; Open woodlands; quercus ilex subsp. ballota; s Management regime